What is new with Artificial Intelligence? Human–agent interactions through the lens of social agency - Pagliari, Marine; Chambon, Valérian; Berberian, Bruno (Frontiers in Psychology, 2022)
The introduction of automated systems, and more broadly of Artificial Intelligence (AI), into many domains has profoundly changed the nature of human activity, as well as the subjective experience that agents have of their own actions and their consequences – an experience that is commonly referred to as sense of agency. In this review, we propose to examine the empirical evidence supporting this impact of automation on individuals’ sense of agency, and hence on measures as diverse as operator performance, system explicability and acceptability. Because of some of its key characteristics, AI occupies a special status in the artificial systems landscape. We suggest that this status prompts us to reconsider human-AI interactions in the light of human-human relations. We therefore approach the study of joint actions in human social interactions to deduce what are the key features necessary to develop a reliable SoA in a social context. We suggest that the study of social interactions and the development of SoA in joint actions can help determine the content of relevant explanations to be implemented in AI to make it "explainable". Finally, we propose possible directions to improve human-AI interactions and, in particular, to restore the SoA of human operators, improve their confidence in the decisions made by artificial agents, and increase the acceptability of such agents.